Comparison of dielectric barrier discharge in air, nitrogen and argon at atmospheric pressure - Tyata, RB; Subedi, DP; Wong, CS (Kathmandu University Journal of Science Engineering and Technology, 2010)
This paper reports the results of electrical characterization of dielectric barrier discharge (DBD) generated in air, nitrogen and argon at atmospheric pressure. Polycarbonate plate of thickness 1 mm was used as a dielectric barrier in a specially designed hemispherical-plane electrode system. A nonuniform filamentary type of discharge was observed in air. Introducing nitrogen and argon gas at controlled flow rate of 1-2 liters / minute resulted a more homogeneous discharge at a frequency of 28 kHz of the AC source. The discharge was investigated for two values of electrode gap of 1 mm and 2 mm by varying the applied voltage. The number of current pulse per half cycle and the magnitude of the discharge current were found to be higher in the case of air discharge in comparison to the discharge in nitrogen and argon. The characteristics of the discharge in air in the absence dielectric barrier was also examined and interestingly it was found that in this case the filamentary discharge turned to a glow discharge for specific value of applied voltage and electrode spacing.